A Numerical Simulation of Mass Transport in Deep Convection over the Tibet Plateau. Issue 2 (April 2020) - Guo, Yanan; Cao, Xiaoqun; Peng, Kecheng; Liu, Bainian
Abstract: By using the WRF-Chem model to simulate a deep convection process that occurred in the eastern part of the Tibetan Plateau, the vertical transport process and main mechanisms of water and ozone in the upper troposphere-lower stratosphere were studied. The air in the lower layer of the troposphere, which is rich in water vapor and low ozone concentration, is transported near the top of the troposphere. The enhancement of convective motion causes the height of the troposphere to rise and the temperature to decrease. Therefore, water vapor is prone to condensation and dehydration, and ice crystals are formed near the top of the troposphere, resulting in a low value zone of water vapor at 100 hPa. By analyzing the distribution of ozone, it is found that there is a high concentration of ozone transported on both sides of the deep convection area. The stronger the convection, the stronger the downward transport. It further explains that this deep convection process not only causes the upward transport of tropospheric air in the deep convection area, but also causes the transport of stratospheric air to the troposphere on both sides of the deep convection area.